Chronic obstructive pulmonary disease (COPD), illness narratives and Elias's sociology of knowledge. (November 2017) - Malcolm, Dominic; Orme, Mark W.; Morgan, Mike D.; Sherar, Lauren B.
Abstract: This paper draws on Elias's sociology of knowledge to provide a critical assessment of illness narratives. Focusing on a cohort of chronic obstructive pulmonary disease (COPD) patients (n = 26), the paper employs a comparative analysis of mixed method data derived from qualitative interviews, quantitative questionnaires, and physiological and accelerometer testing. The article firstly compares four narratives conveyed in interviews with the broader paradigmatic approach to illness narratives and existing COPD-specific studies. It then explores the relationship between these 'stories' and COPD patients' biographical contingencies (e.g. age, wealth, context of diagnosis) and embodied condition (e.g. co-morbidities, lung function), demonstrating how illness narratives are shaped by both broader social structural factors and embodied experience. Invoking Elias we further find that different narrative subthemes are varyingly affected by patients' emotional engagement and ontological security and thus that people are differently enabled or constrained to present illness narratives that are consistent with their broader social and physical condition. Consequently, while narratives, social structure and embodied experience are interdependent, our reading of 'truth' must be sensitive to the social positioning of the 'teller' and the specific content being relayed. The paper therefore presents a more systematic, comparative, bio-psycho-social analysis than has hitherto been produced. Highlights: COPD patients present four illness narratives: chaos, challenge, contrary and coping. Narratives, social structure and embodied experience are shown to be interdependent. Illness narratives depend on perceptions of emotional and ontological security. Assessment of narrative should entail specific content and patients' social position.